Uncovering the knowledge gaps: A survey on human monkeypox infection among men who have sex with men in Nepal - Paudel, Kiran; Gautam, Kamal; Sujan, Md Safaet Hossain; Wickersham, Jeffrey A; Chaudhari, Prashu Ram; Shrestha, Roman (Health Prospect, 2023)
The monkeypox virus (MPX) poses a major threat to the health of people, especially among men who have sex with men (MSM). However, the knowledge regarding MPX among MSM in Nepal is poorly understood. Therefore, the present study aimed to assess the knowledge of human monkeypox among Nepalese MSM. A cross-sectional face-to-face survey was conducted among purposively selected 250 participants (mean age 27.6 ± 8.9 years) in Nepal between October and December2022. The questionnaire comprised of informed consent along with questions covering age, education, and MPX. The findings demonstrated that the majority of MSM in Nepal had poor knowledge of MPX. Around 87% of participants had no idea whether MPX is contagious or not. However, the results call for immediate action to improve knowledge of MSM through health education programs and appropriate interventions to halt the spread of MPX transmission.